2021
DOI: 10.1111/opo.12810
|View full text |Cite
|
Sign up to set email alerts
|

Associations between visual function and magnitude of refractive error for emmetropic to moderately hyperopic 4‐ and 5‐year‐old children in the Vision in Preschoolers ‐ Hyperopia in Preschoolers Study

Abstract: Purpose To evaluate associations between visual function and the level of uncorrected hyperopia in 4‐ and 5‐year‐old children without strabismus or amblyopia. Methods Children with spherical equivalent (SE) cycloplegic refractive error of −0.75 to +6.00 on eligibility testing for the Vision in Preschoolers–Hyperopia in Preschoolers (VIP‐HIP) study were included. Children were grouped as emmetropic (<1D SE myopia or hyperopia), low hyperopic (+1 to <+3D SE) or moderate hyperopic (+3 to +6D SE). Children with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 66 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…98 Because of the paucity of studies that have investigated visual attention 53,75 and visual-motor integration, 27,74,75,80 we could not explore the association between hyperopia and these domains in this review. However, 2 more recent studies 83,99 have reported poorer visual attention and visual-motor integration in those with hyperopia, and these higher functions are promising areas that warrant further investigation. Because fewer than 10 studies were included in our meta-analyses, we could not test for publication and reporting biases, which are likely in observational studies that do not require prior registration.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…98 Because of the paucity of studies that have investigated visual attention 53,75 and visual-motor integration, 27,74,75,80 we could not explore the association between hyperopia and these domains in this review. However, 2 more recent studies 83,99 have reported poorer visual attention and visual-motor integration in those with hyperopia, and these higher functions are promising areas that warrant further investigation. Because fewer than 10 studies were included in our meta-analyses, we could not test for publication and reporting biases, which are likely in observational studies that do not require prior registration.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…39 The impact of increasing uncorrected hyperopia on visual function was further investigated in a secondary analysis of all 4and 5-year-old children who presented for VIP-HIP study eligibility testing (mean age 58 months). 40 Specifically, visual functions were compared among children classified as having emmetropia [<1 D spherical equivalent (SE) myopia or hyperopia], low hyperopia (þ1 to < þ3 D SE), or moderate hyperopia (þ3 to þ6 D SE). Children with amblyopia, strabismus, or 1 D or more of anisometropia or astigmatism were excluded.…”
Section: Selected Outcomes From the Vip-hip Study Associations Betwee...mentioning
confidence: 99%
“…The percentage of children in each group with 1 or more decreased visual functions increased with increasing hyperopia, from 17% of emmetropes, to 39% of low hyperopes, to 66% of moderate hyperopes. 40…”
Section: Selected Outcomes From the Vip-hip Study Associations Betwee...mentioning
confidence: 99%
See 1 more Smart Citation
“…From a study in Aotearoa / New Zealand, Findlay et al 21 call for the Spot vision screener to be added to the current Parr vision test in the national programme to improve the sensitivity and specificity of amblyopia detection in 4-5 year olds. From the USA, Ciner et al 22 found that amongst 4-5 year old children without strabismus or amblyopia, visual acuity, accommodative lag and stereoacuity all reduced with increasing hyperopia; based on these findings, the authors call for near visual function to be routinely assessed in children with hyperopia. In India, Seelam et al 23 report results from a realist evaluation of a school-based eye health programme with a target population of 2 million children.…”
mentioning
confidence: 99%